Consumption and investment values in housing price: a real options approach - Hung, Chih-Hsing; Tzang, Shyh-Weir (International Journal of Strategic Property Management, 2021)
Homeowners can be viewed as the put option holders who can sell housing to lenders when the housing price is lower than its mortgage value and sell houses when the housing price rises above a certain threshold. On the basis of the theory of investment under uncertainty, we model the housing value from the perspective of houseowners who can choose to either live in their houses or switch houses for comfort improvement and price appreciation. We can decompose the housing value into consumption and investment values by exploring parameters affecting housing value and decision making of houseowners. We find that the proportion of investment value to housing value increases with the volatility of the housing market, indicating the possible formation of housing bubbles. In addition, the comfort and utility provided by housing are critical for homeowners to decide whether to sell their houses. The analysis provides policymakers and market participants in the real estate market with insights into the price formation of real estate.